Glutamine Randomized Studies in Early Life: The Unsolved Riddle of Experimental and Clinical Studies - Efrossini Briassouli; George Briassoulis (Clinical and Developmental Immunology)
Glutamine may have benefits during immaturity or critical illness in early life but its effects on outcome end hardpoints are controversial. Our aim was to review randomized studies on glutamine supplementation in pups, infants, and children examining whether glutamine affects outcome. Experimental work has proposed various mechanisms of glutamine action but none of the randomized studies in early life showed any effect on mortality and only a few showed some effect on inflammatory response, organ function, and a trend for infection control. Although apparently safe in animal models (pups), premature infants, and critically ill children, glutamine supplementation does not reduce mortality or late onset sepsis, and its routine use cannot be recommended in these sensitive populations. Large prospectively stratified trials are needed to better define the crucial interrelations of “glutamine-heat shock proteins-stress response” in critical illness and to identify the specific subgroups of premature neonates and critically ill infants or children who may have a greater need for glutamine and who may eventually benefit from its supplementation. The methodological problems noted in the reviewed randomized experimental and clinical trials should be seriously considered in any future well-designed large blinded randomized controlled trial involving glutamine supplementation in critical illness.